PEMBERIAN FORMULASI TRICHOKOMPOS TKKS DENGAN PUPUK NPK PADA PERTUMBUHAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) BERASAL DARI KECAMBAH KEMBAR DI TBM-I - Simbolon, David Firnando; Zuhry, Elza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to determine the effect of the EFB Trichocompost with NPK formulations and get the best formulations for plant growth those derived from immature oil palm twin sprouts plant. The research was conducted experimentally using a randomized block design (RBD), which consists of 5 treatments and 3 replications, from  June 2016 to September 2016 at the Experimental Farm, Faculty of Agriculture, University of Riau, Rimbo Panjang village, Riau Province. Such treatment was: the formulation EFB Trichocompost with NPK, ie: P0 (without fertilizer), P1 (EFB Trichocompost 10 ton / ha + NPK 6 tablets), P2 (EFB Trichocompost 10 ton / ha + NPK 8 tablets), P3 (EFB Trichocompost 20 ton / ha + NPK 6 tablets), P4 (EFB Trichocompost 20 ton / ha + NPK 8 tablets). The parameters measured were the increase of plant height, number of leaves, trunk circumference, midrib length, and petiole length. Data were analyzed statistically using analysis of variance and Duncan's multiple range test at the 5 % level. The results showed implementation of formulations of  20 ton / ha EFB Trichocompost with 8 tablets  NPK was the best treatment on all parameters in immature oil palm plant origin twin sprouts. Keywords: twin sprouts, oil palm, EFB Trichocompost, NPK.